Damage assessment and test results of construction materials of a fire-damaged RC building - Md Abdul Momin; Khondaker Sakil Ahmed; Tanvir Mustafy; Md. Jahidul Islam (Results in Engineering)
This study presents a comprehensive damage assessment technique to evaluate post-fire condition of a two-basement +22-story RC commercial building in Dhaka, Bangladesh. A fire broke out on March 28, 2019, engulfing the 7th, 8th, and 9th floors of the building, resulting in a minimum of 25 fatalities and over 70 injuries. The five-hour-long colossal fire was initiated on the 8th floor of the building and propagated to the adjacent 7th and 9th floors. The structural components of all three floors were damaged though not at the same level. An in-depth technical inspection was conducted visually to assess the fire damages. Concrete cracking at different widths and depths, crumbled tiles and plasters, concrete failure in the roofs, exposed rebars are observed in both structural and non-structural components of those floors. Based on the visual inspection, damage contours of the different zones of the floors are prepared to determine the damage intensity. The assessment primarily showed that 27 % of the 7th floor, 19 % of the 8th floor, and 22 % of the 9th floor were severely burned in which 2–3 % of the structural components were damaged significantly by concrete crushing and exposed rebars. In addition, compressive strength, carbonation depth, ultrasonic pulse velocity (UPV) and rebar tensile strength test were conducted on concrete and rebar specimens taken from the building to understand the effect of fire on the material properties of the existing building. Subsequently, parametric fire analysis has been conducted explicitly to understand the temperature-time characteristics of compartment fire during the fire period of the damaged floor. The parametric fire characteristics claimed that the fire was ventilation controlled and a maximum gas temperature of 1027.3 °C reached to the 7th Floor. The test results and fire analysis indicate that the increase in temperature caused by the fire has a substantial impact on the mechanical properties of the materials. Specifically, the concrete compressive strength and tensile strength of the reinforcing bars are found to be reduced by 8–35 %, and 15 %, respectively which are also verified though the numerical analysis.